Location of the Maxillary Posterior Tooth Apices to the Sinus Floor in an Egyptian Subpopulation Using Cone-beam Computed Tomography - Ragab , Mai Hamdy; Abdalla , Asmaa Yousry; Sharaan, Marwa El-Sayed (Iranian Endodontic Journal, 2022)
Introduction: The aim of this study was to evaluate the location of the apices of the maxillary posterior teeth to the maxillary sinus floor (MSF), the symmetry between both sides and the possible variations between males and females using cone-beam computed tomography (CBCT) in an Egyptian subpopulation. Materials and Methods: CBCT images were collected from 120 patients (240 second premolars, 480 1st and 2nd molars, 1680 roots). The proximity of roots of maxillary second premolar and 1st and 2nd molars to the floor of the sinus was categorized into three categories: inside the sinus floor (IS), touching the sinus floor (TS) or outside the sinus floor (OS). The correlation of the distance with gender was analyzed as well as for symmetry. Friedman’s test was used to compare between different roots and the Dunn’s test was used for pair-wise comparisons when Friedman’s test was significant. The Mann-Whitney U test was used to compare males and females. The significance level was set at P≤0.05. Results: The highest prevalence of roots outside the sinus was found with second premolar (right and left) followed by palatal roots of right and left second molar. In addition, the highest prevalence of roots inside the sinus was found with mesiobuccal roots of maxillary second molar followed by the palatal root of maxillary first molar. There was no statistically significant difference between males and females or between both sides. Conclusion: Neither gender nor side variations regarding the proximity to the maxillary sinus floor were observed.